Y =ax² + bx +c
1) Point (0,7)
7 = a*0² +b*0 +c
c = 7
y=ax² + bx + 7
2) Point (1,4)
4=a*1² + b*1 + 7, ----> 4 = a +b + 7, ------>
a+b= - 3
3) Point (2, 5)
5=a*2² + b*2 + 7, ----> 5=4a+2b +7,---> -2=4a+2b, ---->
-1=2a + b
4)
a+b= - 3, ----> b= -3 - a (substitute in the second equation)
2a+b= -1
2a - 3 - a = -1, ----> a - 3 = -1,
a =2
5) a+b= - 3
2 + b = -3
b = -5
y=2x² - 5x + 7
Answer:
The value of P(AUB) = 0.438
Step-by-step explanation:
Given:
P(A) = 0.36
P(B) = 0.2
P(A∩B) = 0.122
Find:
The value of P(AUB)
Computation:
P(AUB) = P(A) + P(B) - P(A∩B)
The value of P(AUB) = 0.36 + 0.2 - 0.122
The value of P(AUB) = 0.56 - 0.122
The value of P(AUB) = 0.438
The equation would be 90/18 which would give you the cost of 5 dollars per rose
Answer:
1:
p-r/6=-6-(-6)/6=-6+1=<u>-</u><u>5</u>
<u>2</u><u>:</u>
<u>p-</u><u>(</u><u>m-n</u><u>)</u><u>=</u> -1-(-4-4)=-1-(-8)=-1+8=<u>7</u>
3:
(z+y)/2)3=(-5-4)/3=-9/3=<u>-</u><u>3</u>
<u>4</u><u>:</u>
m/6-n=6/6-6=1-6=<u>-</u><u>5</u>
5:
k³-h=3³-(-2)=27+2=<u>2</u><u>9</u>
6:
p-(p-(m-3))=5-(5-(4-3))=5-(5-1)=5-4=<u>1</u>
7:
(k)(k-j)+3=(5)(5-5)+3=5*0+3=<u>3</u>
8.
p²/6-q=6²/6-4=6-4=<u>2</u>
<u>9</u><u>;</u>
zx+3³=6*4+3³=24+27=<u>5</u><u>1</u><u>.</u>
<u>1</u><u>0</u><u>:</u>
<u>y</u><u>+</u><u>z</u><u>-</u><u>(</u><u>y</u><u>-</u><u>x</u><u>)</u><u>=</u>5+4-(5-2)=9-3=<u>6</u>
<u>S</u><u>o</u><u>m</u><u>e</u><u> </u><u>b</u><u>a</u><u>s</u><u>i</u><u>c</u><u> </u><u>r</u><u>u</u><u>l</u><u>e</u><u>s</u><u>:</u>
+. +. +=+
+. * +=+
+. ÷ +=+
+. - +=+
and
+. +. -=add and put sigh of greater one.
-. * +=-sigh
-÷-=+sigh
- - -=add and put - sigh
Answer:A = P(1+r/n)nt
A = 3500(1+.092/4)4t
Step-by-step explanation: